2018
DOI: 10.1021/acs.inorgchem.7b03154
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Spectroscopic Characterization of Americium Complexes Containing the Bis[(phosphino)methyl]pyridine-1-oxide (NOPOPO) Ligand Platform

Abstract: The crystal structures of americium species containing a common multifunctional phosphine oxide ligand, reported for its ability to extract f elements from acidic solutions, namely, 2,6-[PhP(O)CH]CH-NO, L, were finally determined after over three decades of separations studies involving these species and their surrogates. The molecular compounds Am(L)(NO), Am 1:1, and [Am(L)(NO)][2(NO)], Am 2:1, along with their neodymium and europium analogues, were synthesized and characterized using single-crystal X-ray cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…For example, in the solid state, there are only two single crystal X-ray structures reported that contain Am–NO 3 bonds. In these complexes the Am–O NO 3 distances ranged from 2.514 to 2.635(12) Å, 70 , 71 which was in good agreement with our Am–O NO 3 results, 2.50(1) and 2.57(3). To date, we have been unaware of any Cm single crystal structures that contain Cm–NO 3 bonds and no single crystal data of any kind have been reported for Ac.…”
Section: Discussionsupporting
confidence: 90%
“…For example, in the solid state, there are only two single crystal X-ray structures reported that contain Am–NO 3 bonds. In these complexes the Am–O NO 3 distances ranged from 2.514 to 2.635(12) Å, 70 , 71 which was in good agreement with our Am–O NO 3 results, 2.50(1) and 2.57(3). To date, we have been unaware of any Cm single crystal structures that contain Cm–NO 3 bonds and no single crystal data of any kind have been reported for Ac.…”
Section: Discussionsupporting
confidence: 90%
“…Some particles adhered strongly to the C-tape, so milling was employed for extraction when necessary. Once welded to the MiTeGen MicroMounts loop, the entire configuration including the microcrystal specimen was encased in polyester heat-shrink tubing to create a completely nondispersible sample configuration for SCXRD, as has been previously described for radioactive specimens (Corbey et al, 2018). Of nine Pu-containing particles that were extracted from the sediment, four (designated Pu-1, Pu-2, Pu-3 and Pu-4) were of high enough crystalline quality to obtain usable SCXRD data.…”
Section: Plutonium Sample Preparationmentioning
confidence: 99%
“…Despite limited examples of spectroscopic analyses of solid‐state Am 3+ containing compounds, and unlike materials containing 4f elements, the position of absorption and emission bands are known to be highly dependent on the coordination environment around the metal center . This coordination environment dependency often manifests as a red‐shift in the absorption spectrum or as variance in the position of the 5 D 1′ → 7 F 1′ and 5 L 6′ → 7 F 2′ transitions on the order of 10–15 nm, where examples range from 689 nm for 5 D 1′ → 7 F 1′ and 709 nm for 5 L 6′ → 7 F 2′ to overlapping transitions at 690.5 and 700 nm . As such, shifting in the energy levels can lead to significant ambiguity with regard to the assignment of observed luminescent bands.…”
Section: Figurementioning
confidence: 99%